Analisis Faktor yang Berhubungan dengan Perilaku Keselamatan dan Kesehatan Kerja (K3) pada Petugas Kesehatan di RSUD Prof. Dr. W. Z. Johanes Kupang - Dedi Yanto Adriance Muda; Noorce C. Berek; Indriati Andolita Tedju Hinga (Media Kesehatan Masyarakat, 2020)
A good occupational health safety at hospital can reduce the incidence of work accidents and increase the productivity of each officer. This study was to analyze the factors related to knowledge, perceptions and attitudes of health workers with occupational safety and health behavior. The study design was a cross sectional study. The population was 709 people with a simple random sampling technique of 97 people. The inclusion criteria are all health workers who have been selected by all hospital medical personnel who have contact with patients compared to hospital personnel in the field of management, where their presence has a greater risk of experiencing occupational diseases or occupational accidents (doctors, specialists, nurses, midwives and health analysis) and willing to be research subjects by signing the informed consent. Meanwhile, the exclusion criteria were respondents who were not willing to be the subject of research and medical officers who were on leave/sickness/ permission when collecting data. the instrument used was a questionnaire. The results of statistical tests showed p < 0.05, that is, there was a significant relationship between the level of knowledge, attitudes and K3 RS behavior, while the statistical results of the perception level with behavior were p > 0.005. Health and safety behavior of health workers is an action or activity in an effort to prevent occupational diseases and accidents. Therefore, it is hoped that the K3 Hospital can promote health and safety at the hospital regularly with various themes tailored to the needs of the workers.